2023
DOI: 10.3390/app13074327
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Vicious Circle of Pain–Anxiety–Avoidance: The Role of Positive Affect in Endodontic Therapy

Abstract: Patients with a high level of anxiety anticipate extremely intense pain during dental treatment and frequently avoid visiting dentists, showing a tendency to become caught in a vicious circle of pain–anxiety–avoidance. This research aimed to examine whether dental anxiety mediates the impact of pain anticipation before endodontic treatment in the subjective avoidance of future treatments as a function of positive affect (moderating variable). One hundred consecutive patients that required endodontic therapy we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The IDAF-4C score was 2.47 for participants with dentures and 1.71 for those without; the difference was statistically significant (p = 0.004). This finding is probably best explained by the fact that dental anxiety is a barrier to seeking dental care with a negative impact on oral health [21], and also that people with a high level of dental anxiety prefer to have their teeth extracted than restored [6,22]. Therefore, it is suggested that people with a high level of dental anxiety are at risk to become wearers of removable prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…The IDAF-4C score was 2.47 for participants with dentures and 1.71 for those without; the difference was statistically significant (p = 0.004). This finding is probably best explained by the fact that dental anxiety is a barrier to seeking dental care with a negative impact on oral health [21], and also that people with a high level of dental anxiety prefer to have their teeth extracted than restored [6,22]. Therefore, it is suggested that people with a high level of dental anxiety are at risk to become wearers of removable prostheses.…”
Section: Discussionmentioning
confidence: 99%